Media Gambar Berseri : Peningkatan Hasil Belajar Menulis Karangan Deskriptif Bugis Menggunakan Stimulus-Respon Siswa Sekolah Dasar - Andi Agussalim Aj; Syamsudduha Syamsudduha; Arsi Putri Rahmatullah (HUMAN: South Asian Journal of Social Studies, 2022)
Abstract: This study aims to describe the planning, implementation, and evaluation of learning to write descriptive essays using Bugis Stimulus-Response media, this research is expected to provide theoretical and practical benefits. This research is a classroom action research (CAR) which is carried out in two cycles, starting from (1) planning, (2) implementing actions, (3) Observing, and (4) Reflecting. The subjects of this research were the fourth grade students of SDN 5 Mattiropole Lalabata Soppeng as many as 28 students. The data obtained were processed descriptively quantitatively. The data collection techniques in this study were observation, tests, and documentation. The results of this study indicate that the learning outcomes of students' Bugis regional language using the Stimulus-Response media of serial images of fourth grade students of SDN 5 Mattiropole have increased. This can be seen from the final test scores of students in the first cycle, 18 students or 78.26% were declared complete, and the last test scores in the second cycle increased with 21 students or 91.30% completeness. The results showed that there was an increase in learning outcomes to write Bugis descriptive essays in the first cycle in the good category, and the second cycle in the Very Good category, while the observations of teacher and student activities were in the good category. The conclusion in this study is the result of writing descriptive essays using Stimulus-Reapon Bugis. Serial image media for fourth grade students of SDN 5 Mattiropole Lalabata Soppeng Increases. Keywords: Learning Outcomes to Write Descriptive Essay